Rintisan Bank Sampah Dasawisma Untuk Kesehatan, Ekonomi, Dan Lingkungan Lebih Baik - Shinta Wurdiana Rhomadona; Eny Astuti; Dian Purnama Sari (Universitas Merdeka Surabaya, 2026)
A Waste Bank in RW 07 was undertaken, involving women from the Family Welfare Empowerment (PKK) group as key drivers. The objective was to enhance community knowledge, skills, and awareness in household waste management while strengthening health, hygiene, and family economy for a better environment. The stages and methods of community service (PkM) implementation in Tambak Dono Village RW 07 included counseling, training, demonstrations, and mentoring for one month. To ensure sustainability, advocacy was carried out with RW officials to support continuous operation of the waste bank. The partner community actively participated by providing environmental data, assisting in coordination, supplying activity venues, and serving as waste bank administrators. The program outputs included increased partner empowerment levels, a scientific article for submission to a nationally accredited journal, activity videos, posters, online media publications, and a guidebook. The main outcomes were the establishment of the RW 07 Tambak Dono Waste Bank managed by PKK members, increased household participation in waste sorting between organic and inorganic materials, and the creation of simple recycled products such as ecobricks. The Dasawisma group became actively involved in collecting and selling economically valuable waste such as used cooking oil. Based on pre- and post-activity questionnaires, residents’ knowledge and awareness increased by 90%. Scientific publications and media outputs have been prepared as deliverables for the current year.